Biscuit, cookie and cracker production : process, production and packaging equipment - Davidson, Iain (Academic Press, 2019)
Biscuit, Cookie, and Cracker Production: Process, Production, and Packaging Equipment is a practical reference that brings a complete description of the process and equipment necessary for automated food production in the food/biscuit industry. The book describes the existing and emerging technologies in biscuit making and production, bringing a valuable asset to R & D personnel and students in food technology and engineering areas. Full of clear illustrations, photos and text describing types of biscuits, cookies and crackers, ingredients, test bakery equipment, dough piece forming, biscuit baking ovens, biscuit cooling and handling, and processing and packaging, this book presents a timely resource on the topic. Covers the complete processed food production line, from raw materials to packaged product.